Pressure effect on intermediate structures during transition from amorphous to crystalline states of copper - Kazanc, S.; Celik, F. A.; Yidiz, A. K.; Ozgen, S. (Elsevier Science Bv, 2007)
This study presents a molecular dynamics simulation to investigate the pressure effect on the rapid and slow solidification of Cu in liquid state within Sutton-Chen type of the embedded atom method (EAM) potential. To determine temperatures of glass and crystal formation for the model system, radial distribution function (RDF), the changes of volume and Wendt-Abraham parameters are calculated for different pressures. Crystal and amorphous transitions for different pressures are formed at cooling rate of 4 x 10(12) K/s and 4 x 10(13) K/s, respectively. It is observed that the increase of pressure causes an increase of glass and crystal formation temperatures. Moreover, the local structures of the system are analysed by bond orientational order parameters to distinguish the simple structures in the system. It is observed that a higher pressure leads to a strong crystallization for lower cooling rate, but the glassy Cu forming for higher cooling rate at the same pressure have decreased icosahedral order, enhanced others clusters. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: embedded atom method; rapid solidification; molecular dynamics simulation; bond orientational order